Determining the chemical composition and in vitro digestibility of forage species used in small ruminant production systems in the english speaking Caribbean - Part 1 - Cranston L (University of West Indies Press, 2021)
The nutritional evaluation of tropical forages in the Caribbean is limited. Therefore, this study was done to provide information on the nutritive value of 12 forages used in regional small ruminant production systems in the Caribbean region, utilising three different methods of forage evaluation. Samples of seven grasses Brachiaria arrecta, Brachiaria ruziziensis, Cynodon dactylon, Cynodon nlemfuensis, Digitaria eriantha, Megathyrsus maximus and Pennisetum purpureum; two leguminous multipurpose tree species (LMPTs) Gliricidia sepium and Leucaena leucocephala and three non-leguminous multipurpose tree species (NLMPTs) Moringa oleifera, Morus alba and Trichanthera gigantea were collected from one of two sites located in Trinidad and Jamaica. Analysis of nutritive value was done using proximate analysis, in vitro assays and near infrared spectroscopy (NIRS). Cynodon nlemfuensis had the highest crude protein (CP, 191.2 g/kg DM) of the grasses and Leucaena leucocephala and Moringa oleifera the highest CP (263.6 and 232.5 g/kg DM respectively) of the LMPTs and NLMPTs. The NLMPTs, Moringa oleifera and Morus alba had the highest starch, highest in vitro digestible organic matter in dry matter (IVDOMD, 651 and 655 g/kg DM respectively) and metabolisable energy (ME, 10.62 and 10.68 MJ/kg DM respectively) and the lowest neutral detergent fibre (NDF) of the MPTs. There was a strong positive relationship between the IVDOMD and both the CP and starch fractions and a strong negative relationship between the IVDOMD and both the NDF and acid detergent fibre (ADF) fractions. The NIRS predicted values had a strong relationship with the gross chemical CP, NDF, IVDOMD and ME) values of tropical forage species (R2 = 0.91, 0.86, 0.70 and 0.80 respectively). Overall, the forage species were above the minimum CP, IVDOMD and ME required to be classified as intermediate to good quality forages.
Keywords: 0703 Crop and Pasture Production